Pengaruh pengencer komersial terhadap motilitas dan viabilitas spermatozoa semen babi landrace yang disimpan pada temperatur berbeda - Maria B.L Ma; Nancy D. F. K. Foeh; cynthia D Gaina (Jurnal Veteriner Nusantara, 2019)
The objective of this study was to determine the the effect diluent of commercial is diluent BTS® and MIII® in maintaining sperm motility and viability of landrace boars during storage at different temperatures at refrigerator (5 °C), AC (28 °C) and room temperature (32 °C). This experiment used a completely randomized design (CRD) with 6 treatment and 4 replications. Semen was collected twice a week from landrace boars. Semen Characteristic and their quality were evaluated macroscopically and microscopically. Good quality semen have motility >70%, sperm concentration 200 x 106 sperm/ml and morphological abnormality less than 20%, these semen were added with diluent commercial is diluent BTS® and MIII®. Sperm motility and viability were evaluated every 2 hours until 40% motility were evaluated. The result showed that fresh semen characteristic were good, with the presentage of sperm motility 85% with sperm concentration 242.50±16.5% and morphological abnormality 12.50±1.70%. The results showed that the liquid semen of landrace boar were stored at a temperature of 28 °C is better results temperature with the percentage motility of sperm 54.50% during 38 hours and temperature of 5 °C showed the second best result with the percentage of 46.32% motility during 36 hours of storage in the diluent BTS® . In conclusion : BTS® diluent is an appropriate diluent used to maintaining semen quality of landrace boars quality during preservasion.